Information Search Behavior: Concepts and Terminology (The International Journal of Educational Sciences and Arts, 2025)
This study aims to analyze concepts and terminology related to information seeking behaviors by reviewing the scientific literature and reviewing the different definitions of each term. The study relied on the conceptual analytical approach, where the basic terms were collected and analyzed. The study focused on identifying the most prominent terms used in the field, providing clear definitions for each, and representing them visually to facilitate their understanding and clarify their meanings. The study also analyzed the relationships between these concepts and their interactions within the scientific context, enabling the construction of a proposed model that integrally illustrates the links between the terms. This model promotes a comprehensive understanding of information-seeking behaviors and paves the way for a unified and effective use of these terms in future research. The study recommended further studies to analyze the information-seeking behavior of beneficiaries, focusing on their needs and motivations. It is also advisable to expand conceptual studies on the terminology of information-seeking behavior and to build models of interactions between different concepts and test them in applied contexts.
Keywords: Information Search Behavior; Information Seeking Behavior; Search Behaviors; Information Awareness; Need for Information; Knowledge Seeking Behavior